PERANAN DEWAN KEHORMATAN DAERAH TERHADAP PENEGAKAN KODE ETIK NOTARIS DI KABUPATEN TULUNGAGUNG - , SEQLY INTAN MAYANG SAKTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the sanction by the WCA Board of Trustees to the notary who violates the code of ethics in Tulungagung, and to know the efforts of the Honorary Board of Trustees of Regional in Tulungagung to overcome obstacles or barriers in carrying out its role The. This type of research used in this study was Juridical Empirical Research. The research was conducted through direct interviews with respondents and equipped with secondary data. The sampling technique used was nonprobability sampling technique with sampling purposive sampling. Data analysis was done by using a qualitative approach. The results of the data analysis are presented descriptively. These results indicate that the code violations Tulungagung still plenty going on, but to penalize the only form of warning and guidance is less effective so it does not provide a deterrent effect for the notary and the notary does not provide lessons for other-notary. In addition to the establishment of the Honorary Board of the Regional yet Tulungagung resulted in maximal supervision for violation of code of conduct. Many of the constraints faced by the Regional Supervisory Council include notary notary-less cooperative and assume all code violations are considered reasonable and has become a habit for generations, as long as there has been no case of sticking out because of all the direct resolved internally. Efforts made Honorary Board and Supervisory Council Notary in overcoming obstacles in order to uphold a code of ethics among others, are as follows: (a) Provide regular counseling to the notary on the code of conduct violations that often occur